The Effectiveness Test Of Moringa Leaf Extract (Moringa oleifera) As Antifungal Against Candida albicans Growth (Literature Review) - Raudah, Siti; Anam, Khoirul; Iqbal, Muhammad (Jurnal Teknologi Laboratorium Medik Borneo, 2025)
Moringa leaf extract (Moringa Oleifera) contains essential oils, and the main compounds that can be used as antifungals include flavonoids, alkaloids, phenols, proteins, sapanoids, tannins and terpenoids. In this literature review, the fungus used is Candida albicans with the type of extraction solvent, such as ethanol with various concentrations. Purpose: To determine the effectiveness of Moringa leaf extract in ethanol solvents with various concentrations in inhibiting the growth of Candida albicans. Method: Search literature reviews with research topics to answer existing issues or problem. The year of publication was between 2010 and 2021. The search started from January 14, 2021, to March 17, 2021, through an electronic search based on the Garuda Portal, Google Scholar, Google Search, and PubMed. Result and Discussion: 7 journals or articles obtained. Two journals showed an inhibition zone that occurred from Moringa leaf extract on Candida albicans growth with 90% ethanol solvent producing an inhibition zone of 3.0 mm and 95% ethanol solvent producing the highest inhibition zone of 14 mm, wich showed the effectiviness of Moringa leaf extract (Moringa Oleifera) on the growth of Candida albicans. In comparison, the other five journals did not show any inhibition zones formed, which showed no effect of Moringa Oleifera leaves on the growth of Candida albicans. Conclusion: Moringa leaf extract with 90-95% ethanol solvent show inhibition against Candida albicans